Método para determinação dos níveis de maturidade de transferência de tecnologia dos núcleos de inovação tecnológica brasileiros - Soares, Adriano Mesquita (2020)
levels of Technology Transfer Offices (TTO) in Brazil. For this, an applied research was carried out with quanti-qualitative method and descriptive approach. The technical procedure format was a survey. Technology Transfer specialists were responsible for attaching weight to such elements as criteria, dimensions and variables using the multicriteria method, Fuzzy Simple Additive Weighting. Results have highlighted a pointed focus on the process of protecting technology contrasting to developed countries TTOs’ main focus. Results also provided an important overview of 105 Brazilian TTOs, their maturity level and the impact on social and economic development. Even though this method has proven to be a comprehensive way of providing meaningful information for TTOs managers and developing countries policy makers, future studies can address new evidences from developing countries.